Pete the cat's train trip - Dean, James 1957- (Harper, an imprint of HarperCollinsPublishers, 2015)
Embarking on a train trip to visit his grandmother, Pete the Cat accompanies the conductor on a tour of the train, looks at the engine and blows the whistle while making new friends and playing train-themed games
Keywords: Pete -- the Cat (Fictitious character) -- Juvenile fiction; Fiction; Juvenile works; Cats; Railroad travel; Railroad travel -- Juvenile fiction; Cats -- Juvenile fiction; Eisenbahnreise; Kinderbuch; Bilderbuch